Incidence of Medically-Attended Norovirus-Associated Acute Gastroenteritis in Four Veteran's Affairs Medical Center Populations in the United States, 2011-2012. - Scott P Grytdal (PLoS ONE, 2015)
An estimated 179 million acute gastroenteritis (AGE) illnesses occur annually in the United States. The role of noroviruses in hospital-related AGE has not been well-documented in the U. S. We estimated the population incidence of community- acquired outpatient and inpatient norovirus AGE encounters, as well as hospital-acquired inpatient norovirus AGE among inpatients at four Veterans Affairs (VA) Medical Centers (VAMCs). Fifty (4%) of 1,160 stool specimens collected ≤7 days from symptom onset tested positive for norovirus. During a one year period, the estimated incidence of outpatient, community- and hospital-acquired inpatient norovirus AGE was 188 cases, 11 cases, and 54 cases/ 100,000 patients, respectively. This study demonstrates the incidence of outpatient and community- and hospital-acquired inpatient norovirus AGE among the VA population seeking care at these four VAMCs.